Pengenalan Konsep Filosofi Hidup Ikigai kepada Generasi Z sebagai Bentuk Memaknai Hidup di Era Digital - Umi Handayani; Rosalina Wahyu Riani; Priventa, Hendrike (PELITA NUSA TENGGARA, 2023)
The concept of ikigai is a philosophical concept originating from Japan regarding the human perspective on life. The four components of ikigai are mission, passion, profession, and vocation. The function of ikigai is to form individual personalities who can understand life in terms of things that need to be prepared from a young age. The purpose of this service activity is to provide an introduction to generation Z about the concept of ikigai. The method used is giving pre-test and post-test. The results obtained were that 65% of the participants could understand the ikigai concept that had been given.